2010
DOI: 10.1074/jbc.m110.167619
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Heme-responsive Element Mediates Transcriptional Regulation in Caenorhabditis elegans

Abstract: Hemes are prosthetic groups that participate in diverse biochemical pathways across phylogeny. Although heme can also regulate broad physiological processes by directly modulating gene expression in Metazoa, the regulatory pathways for sensing and responding to heme are not well defined. Caenorhabditis elegans is a heme auxotroph and relies solely on environmental heme for sustenance. Worms respond to heme availability by regulating heme-responsive genes such as hrg-1, an intestinal heme transporter that is up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 37 publications
2
21
0
1
Order By: Relevance
“…In addition, microarray analysis and qRT PCR studies show that mrp-5 is itself a heme responsive gene as its mRNA increased over 3-fold under low heme conditions (Severance et al, 2010). Indeed, in silico analysis of the putative mrp-5 promoter revealed the presence of a canonical 23-base pair heme response element, which we have previously shown is necessary and sufficient to mediate heme dependent regulation of hrg-1 in the worm intestine (Sinclair and Hamza, 2010). …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, microarray analysis and qRT PCR studies show that mrp-5 is itself a heme responsive gene as its mRNA increased over 3-fold under low heme conditions (Severance et al, 2010). Indeed, in silico analysis of the putative mrp-5 promoter revealed the presence of a canonical 23-base pair heme response element, which we have previously shown is necessary and sufficient to mediate heme dependent regulation of hrg-1 in the worm intestine (Sinclair and Hamza, 2010). …”
Section: Resultsmentioning
confidence: 90%
“…By individually depleting 288 heme-responsive genes, which included 41 genes encoding transmembrane-domain containing proteins, we uncovered mrp-5 (F14F4.5) as a potent regulator of the C. elegans transgenic heme sensor strain, IQ6011. The IQ6011 strain expresses GFP in the intestine from the heme-responsive hrg-1 promoter; GFP levels in this strain are inversely correlated with heme levels in the worm (Rajagopal et al, 2008; Sinclair and Hamza, 2010). Depletion of mrp-5 in IQ6011 by RNAi resulted in significantly greater GFP levels compared to control RNAi, indicating that loss of mrp-5 results in the animal sensing less heme (Figure 1B; and (Severance et al, 2010)).…”
Section: Resultsmentioning
confidence: 99%
“…Nutritional studies investigating how C. elegans was able to survive in low heme medium revealed that heme deficiency led to the increased expression of 117 genes [59]. Further analysis of two of these genes, named hrg-1 and hrg-4 for heme-regulated gene 1 and 4, revealed that they encoded transporters that are required for the absorption of dietary heme from the intestine [59, 60]. Notably, homologs of these genes have similar roles in heme transport in mammals [59].…”
Section: Transcriptional Control Of Metal-homeostasismentioning
confidence: 99%
“…Heme regulates the transcription of several genes by binding to specific cis Heme Responsive Elements (HRE) 40 and/or by controlling the activity of specific transcription factors. Moreover, heme controls translation through the heme-regulated eIF2α kinase (HRI) 41 and it enhances the efficiency of pri-miRNA processing by binding and promoting the dimerization of the RNA-binding protein DiGeorge critical region-8 (DGCR8).…”
Section: Regulatory Roles Of Heme During Erythroid Differentiationmentioning
confidence: 99%